THE EFFECT OF WRIST POSTURE AND FOREARM POSITION ON THE CONTROL CAPABILITY OF HAND-GRIP STRENGTH - Liao, Kun-Hsi (International Journal of Industrial Engineering: Theory, Applications and Practice, 2014)
Economic and industrial developments have yielded an increase in automated workplace operations; consequently, employees must learn to operate various hand tools and equipment. The hand grip strength exerted by workers during machinery operation has received increasing attention from engineers and researchers. However, research on the relationship between hand grip strength and posture—a crucial issue in ergonomics—is scant. Therefore, in this study, the relationships among wrist posture, forearm position, and hand grip strength were examined among 72 university students. Three wrist posture and forearm positions of grip span were tested to identify the maximum volitional contraction (MVC) and hand gripping control (HGC) required for certain tasks. A one-way analysis of variance was conducted using MVC and HGC as dependent variables, and the optimal wrist posture and forearm position were identified. The findings provide a reference for task and instrument design and protecting industrial workers from diseases.